Burkina Faso : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments on Burkina Faso during 1994-98. Real GDP growth increased sharply following the 1994 CFA franc devaluation from an average of 0.8 percent in 1992-93 to an average of 4.2 percent in 1994-97. As a result, the decline in real terms of GDP per capita was reversed. In the mining sector, value added is estimated to have increased by about 10 percent in 1997, but official production of gold remains significantly below the level before 1994.